Twisted shadows - Therin, Allie (A sugar & vice novel, 2024)
"In a thrilling alternate-universe Seattle, empaths are disappearing--and it's up to grumpy Reece and his mysterious protector, Grayson, to investigate. Empath hunter Evan Grayson is the Dead Man, transformed by a dark past into a perfect weapon against corrupted empaths. Nothing can distract him from stopping these superhuman killers--until he's mired in a new battle, fighting a forbidden attraction to an empath on the verge of corruption. For pacifist Reece Davies, every day is a struggle to keep his darker side in check. It's only his complicated relationship with Evan that keeps him grounded--a relationship that, despite his growing feelings, must stay at arm's length. But when an empath's murder on the East Coast points to a treacherous plot back west, with Reece as the next potential target, Evan races across the country to be by his side. Together, they search for missing empaths, their proximity heightening the chemistry they must resist. But corruption isn't the only danger they face as sinister forces close in from the shadows, sights set on empath and empath hunter alike..."--Back cover.